The Influence of External Financing, Book-Tax Differences, and Product Diversification on Profit Management Moderated by Managerial Ability - Moh. Ardan Makarim Corny; Christina Dwi Astuti (Green Publisher Indonesia, 2025)
This study aims to examine the influence of external financing, book-tax differences, and product diversification on earnings management, with managerial ability as a moderating variable. The data used are panel data from 60 Bursa Efek Indonesia (BEI) infrastructure sector companies from 2019 to 2023, totaling 198 observations obtained using purposive sampling techniques. The results of the study, using the fixed effects model, provide empirical evidence of a significant negative relationship between external financing and earnings management, thus supporting signaling theory and emphasizing the importance of financial reporting transparency to reduce opportunistic earnings management practices. Conversely, book-tax differences have a significant positive effect on earnings management, illustrating how management weighs costs and benefits according to rational choice theory and the existence of principal-agent problems for personal gain. Product diversification has no effect on earnings management. Furthermore, managerial ability is only able to moderate the effect of external financing on earnings management by strengthening the negative relationship between these two variables.